(untitled) (Journal of Medicine, 2017)
Hypertension is the most prevalent chronic disease in India and its prevalence is rapidly increasing among urban and rural populations. Reducing blood pressure can decrease cardiovascular risk and all cause mortality. This study was conducted to assess the efficacy and safety of fixed dose combination of Olmesartan 40 mg and Chlorthalidone12.5mg. 30 hypertensive patients having systolic blood pressure ? 160 mmHg and diastolic blood pressure ?100 mmHg who were uncontrolled on monotherapy with olmesartan were enrolled in this study. The treatment period was of 60 days and patients were administered once daily fixed dose combination of Olmesartan40 mg and Chlorthalidone 12.5 mg. Patients were evaluated on 15th, 30th and 60th days of treatment.There was statistically significant (p<0.0001) decrease in systolic blood pressure from baseline to 15th, 30th and 60thday of treatmentmean±SD (179.1±13.38 mmHg vs. 169.3±13.05, 154.3±13.31, and 142.7±6.91mmHg) respectively. Similarly the diastolic blood pressure (DBP) was significantly (p<0.0001) reduced from the baseline to the 15th, 30th and 60thday of treatment (94.97±5.75mmHg vs.86.67±4.79, 80.33±1.82 and 76.7±4.32 mmHg respectively). Thus fixed dose combination of Olmesartan and Chlorthalidonewas found to be effective and safe option for the optimal management of hypertension. J MEDICINE January 2017; 18 (1) : 6-9